3(k-4)-2(k+2)-14=-22

Simple and best practice solution for 3(k-4)-2(k+2)-14=-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(k-4)-2(k+2)-14=-22 equation:


Simplifying
3(k + -4) + -2(k + 2) + -14 = -22

Reorder the terms:
3(-4 + k) + -2(k + 2) + -14 = -22
(-4 * 3 + k * 3) + -2(k + 2) + -14 = -22
(-12 + 3k) + -2(k + 2) + -14 = -22

Reorder the terms:
-12 + 3k + -2(2 + k) + -14 = -22
-12 + 3k + (2 * -2 + k * -2) + -14 = -22
-12 + 3k + (-4 + -2k) + -14 = -22

Reorder the terms:
-12 + -4 + -14 + 3k + -2k = -22

Combine like terms: -12 + -4 = -16
-16 + -14 + 3k + -2k = -22

Combine like terms: -16 + -14 = -30
-30 + 3k + -2k = -22

Combine like terms: 3k + -2k = 1k
-30 + 1k = -22

Solving
-30 + 1k = -22

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + 1k = -22 + 30

Combine like terms: -30 + 30 = 0
0 + 1k = -22 + 30
1k = -22 + 30

Combine like terms: -22 + 30 = 8
1k = 8

Divide each side by '1'.
k = 8

Simplifying
k = 8

See similar equations:

| 19m=10 | | -4n+18=-3n-5 | | 2n/8=2/5 | | -6-2+8=-11-5p | | 6x-10+2x+8= | | 2p/8-20=-30 | | K^2+12k-16=-3 | | 5*x-8*x=60 | | (-8z+4)+(7z-7)= | | 8x-(2x-3)=3(x-4) | | 0.75-1/2(1/2-3) | | -4(p+9)=24.8 | | 7x-44=13+4x | | 2x-4+x+8=180 | | 6(x-5)=66/11 | | 11y*y= | | 6(6-5)=66/11 | | x+16=4x-7 | | 31=-.06m | | 29b^2+48-88b=0 | | Log[5](x-3)-log[5](x+4)=2 | | (6+3d)-3d=-10 | | 13(7x-8)=9x-6 | | 17x+48=180 | | -7(7x+5)-5= | | 31=-.06 | | 6(2v)= | | 3(4/9)-5y=1 | | (2/3)z=4(1/4) | | g(6)=-2x+4 | | 15x^2-12x-99=0 | | 11v+8=9v-18 |

Equations solver categories